2019
DOI: 10.21276/ijcmr.2019.6.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Automated Analyzer Generated Red Blood Cell Parameters and Histogram with Peripheral Smear in the Diagnosis of Anaemia

Abstract: Introduction: Red blood cell (RBC) indices and histogram obtained from automated analyzer give an idea about morphological changes in anaemia. Along with the peripheral smear, they can be used to interpret the cause of anaemia. The aim of the present study was to correlate typing of anaemia based on RBC indices and histograms obtained from automated analyzer with peripheral smear examination and to give a better approach in the diagnosis of anaemia and analyse their limitations. Material and methods: Blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…Out of the 1000 cases of anemia included in our study, we observed a higher prevalence in females, with 52.7% of the cases being female. This finding is consistent with past research conducted by Singhal et al 13 and Garg et al, 4 where they reported female predominance with 64.9% and 62.9% cases, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Out of the 1000 cases of anemia included in our study, we observed a higher prevalence in females, with 52.7% of the cases being female. This finding is consistent with past research conducted by Singhal et al 13 and Garg et al, 4 where they reported female predominance with 64.9% and 62.9% cases, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…3 The RBC histogram is generated by the automated hematology analyzer, which uses sophisticated technology to measure the size and number of red blood cells in the blood sample. 4 The normal histogram curve generated by the automated hematology analyzer is typically bell-shaped and symmetrical, indicating a Gaussian distribution. This normal curve represents the range of mean corpuscular volume (MCV) between 80-100fl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total blood count test can give an overview of the patient's general health state because abnormal blood counts can be an indication of the existence of many different diseases [ 6 ]. Using advanced hematology analyzers and a traditional microscopic examination of a peripheral blood smear might reveal vital details about a patient's clinical status [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional microscopic examination of peripheral smear for red blood cell morphology provides crucial information about the patient's clinical condition and has always been the cornerstone of diagnostic haematology. 1 However, laboratory haematology has been labour intensive and time consuming. 2 Over the past few years, complete blood count by the automated haematology analyser and peripheral blood smear have complemented each other to provide a comprehensive report on the patient's blood sample.…”
Section: Introductionmentioning
confidence: 99%